PERANCANGAN PROGRAM KEDATANGAN DAN KEBERANGKATAN KAPAL PERIKANAN DI PELABUHAN PERIKANAN NUSANTARA KARANGANTU - Ma sum; Waliadi Gunawan; Irma Yunita Ruhiawati (JURNAL SATYA INFORMATIKA, 2022)
The purpose of this study is to further ease in accessing the data - the data and preparing reports required by the parties - those in need . The method used in this study is the waterfall method ( waterfall model) that begins with research on a running system , design , coding , and maintenance of records management system that archives information management and records management report generation can run fast , precise and accurate . The results obtained from this study is the management information system that is integrated with the database records to support records management process easily , quickly , and accurately .The conclusion that can be drawn from this information system that records management can be well documented because it is equipped databases , storage has become a single entity , can reduce redundancy or duplicate data, it can display the file management information is needed so as to facilitate officers in preparing reports of record-keeping . For this reason , the authors take the title of real practice ( PKN ) is as follows: "RECORDS MANAGEMENT SYSTEM ANALYSIS OF FINANCIAL MANAGEMENT DEPARTMENT OF REVENUE AND PROVINCIAL BANTEN "